The Pedagogic Discourse of the Greek School Science Textbooks of Primary and Lower Secondary Level - Koulaidis, Vasilis; Dimopoulos, Kostas (Παιδαγωγικά ρεύματα στο Αιγαίο, 2022)
The aim of this paper is the mapping of the pedagogic discourse in the Greek school science textbooks of the primary and lower secondary level. School science textbooks are considered as means of regulating the pedagogic discourse of each of the educational levels. This approach stems from the view that science education (and education in general) is a socialization process into the practices and conventions (i.e. the discourses) of sub-communities, in our case of the scientific community (Lemke, 1990). Within the framework of this view, science textbooks have a central role to play in this socialising process as a resource for shared meaning making (Lemke, 1990; Bazerman, 1998).